From 1963 to 2013, from Umberto Pallotta, Pompeo Capella and Edoardo Turchetto to the future: “Lipids in 50 years of research - Cocchi, Massimo (Progress in Nutrition, 2014)
After 40 years since I entered the glorious Institute of Biochemistry, University of Bologna and began to deal with lipids, fatty acids and their tissue and cellular metabolism. That was the time of the demonization of saturated fat and cholesterol; substances that were considered “hurt” the body. I must say, for intellectual honesty, that our “School” never for a moment believed in this axiom, as documented in the long sequence of scientific papers produced. Even science as politics is often dominated by movements of thought and leadership affected by interests that have little to do with the knowledge of phenomena, with a genuine scientific speculation, documented and critics. However, it is not this, the time of polemics but to restore some truth, that not only give confidence to those who believe in science, but that lead back the thought and knowledge in the right direction. This is the case of fatty substances, of the lipids that with the daily eat, with the worry of mind, almost religious, committing sin. Even in science, with the economic power and the misuse of the mathematical discipline called statistics, you can prove everything and support it in the face of scientific, complacent, communities. Well, Aseen Malhotra, says in his “observations” in the British Medical Journal: “Correlation” does not mean “Cause”. Lipids, fatty acids and cholesterol are living a new course, their roles and functions are restoring, roles and functions that, too often and superficially, have been addressed and discussed. During those glorious years in the Biochemistry of Bologna we realized that most of the phenomena related to the “lipid handling” should be interpreted through the behavioral study of biological membranes and the relationships that they contracted between the inside and outside of the cell. We were, from the beginning, convinced that it was inappropriate to make excessively fluid the cell membranes and that it was also inappropriate to demonize saturated fats and cholesterol. Even, and especially from them, depended the functioning of regulatory activities, in the biochemical sense, of the cellular traffic. Today, with searches that investigate the man and the animal, with a simple blood test, and with the aid of complexes mathematical tools, which can not be manipulated, many of the phenomena which was convinced are confirmed for a role of saturated fat and cholesterol as essential agents in the control of the correct function of the membrane which, however, does not tolerate nor extreme excesses or deficiencies, to the detriment of dysregulation of the entire biochemical system. The drastic elimination of the visible fat from foods of animal origin and the push for more and more desired reduction in serum cholesterol will dispense, with both hands, rebound of clinical problems, to say the least, devastating. The different chapters of research addressed, faced the lipid and fatty acids research in various experimental conditions: cell culture, animal, man. Below is summarized the search path made up to the latest experimental evidence in areas that have proved indispensable links with lipids and in particular with fatty acids. The study of lipids, and of the fatty acids of tissues and cells, allows important nutritional and diagnostic interpretive skills, as well as has been proved essential, on some occasions, the use of complex mathematical functions (Artificial Neural Networks) to the understanding of phenomena that otherwise would not have been possible, and that led to the opening of new frontiers of knowledge in biological and clinical conditions of high complexity. They involve the heart and the brain.